Examples of neogene volcanism in eastern Turkey: Comparative petrographic, geochemical and petrologic features of Malatya-Elazig-Tunceli volcanics - Kürüm, Sevcan; Akgül, Bünyamin; Erdem, Emin (My University, 2006)
Neogene-age volcanics having within plate character widely outcrop in the east Anatolia region. Complex zonation indicating magma mixing is commonly observed in petrographic sections. Geochemical data shows that these volcanics are alkalic, calc-alkalic and tholeiitic in character. Three possible sources responsible for the composition of these volcanics are fractional crystallization of a mafic magma, magma mixing and crustal contamination resulting from continent - continent collision. © Geol. Soc. India.
Keywords: Anatolian volcanics; Eastern Turkey; Elazig-Tunceli area; Geochemistry; Neogene; Petrography